Artificial Intelligence and Privacy Breaches: A Socio-Legal Analysis of Digital Crimes against Women in India - Singh, Sunidhi; Ahmed, Sufiya (Frontiers in Law, 2026)
The issue of Digital Crimes Against Women in India is a growing concern within society today due to the rapid growth of Internet Access throughout the Country, as well as Digital Technologies. Within this discussion are some of the most common types of Digital Crime Against Women including Cyber-Bullying, Trolling and the abuse of Deep Fakes. Cyber-Bullying is defined as the intentional act of using Digital Platforms to abuse or threaten or degrade women through harassment. This has been shown to cause significant Psychological Distress for many women. Trolling is another common form of Digital Crime that occurs to women. This is the posting of inflammatory statements or comments meant to incite emotional responses and create further marginalization for women in Online Spaces. With the introduction of Deep Fake Technology, this has created an additional dimension of Digital Harassment. The objective of this paper is to explore the Multidimensional Nature of Digital Crime against Women in India. Digital Crimes will be examined through cyber-bullying, trolling and deep fakes. This paper enhances the current body of Law in India by showing where India’s Digital Laws are deficient regarding AI-based and Deepfake-generated Gendered Harms. In addition, it proposes to create additional Targeted Technology-Specific Regulations to protect Women’s Digital Privacy and Dignity.